The effect of wind load on roof truss system - Nur Alif, Ismail (2014)
Nowadays there are lots of constructions that will be constructed in Malaysia. One of the considerations in design is wind load. From the past record, one of the top ten natural disasters occurred in Malaysia is wind storm. However the understanding of wind behavior to roof truss system is not well defined. Numbers of failure cases has been reported in mass media. Wind storm has caused many failures to structure especially to roof truss system. The previous study shows that the maximum load that can be support by each joint is 6.80kN. Finite Element Software was used in this study to analyze and identify the load distribution of the truss system. Two type of typical truss were used in this study. From the result, type 1 wills possibility fails at 30.34 m/s while type 2 able to resist maximum wind speed recommended in MS 1553:2002. Therefore it can be conclude that the arrangement of truss system will be affected to generate damage. Further study needed to be conducted in future.